2015
DOI: 10.1007/s12540-015-1016-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of microstructure and texture of cast and homogenized TX32 magnesium alloy after hot deformation

Abstract: The effect of homogenization on the hot deformation behavior and texture evolution of Mg-3Sn-2Ca (TX32) alloy is investigated. The cast-homogenized alloy samples were hot compressed in the temperature and strain rate ranges of 300-500°C and 0.0003-10 s -1 , respectively, and a processing map has been developed by using the flow stress data. The map revealed two dynamic recrystallization (DRX) domains with a peak efficiency of 44% at 360°C/0.0003 s -1 (Domain 1) and 43% at 485 ○ C/0.1 s -1 (Domain 2). When comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Magnesium alloys, which have high specific strengths and low densities, are increasingly attracting attention because of their potential for use as materials for lightweight structural components [1][2][3]. However, such alloys exhibit poor formability at low temperatures, owing to the fact that their numbers of activating slip systems are insufficient to satisfy the von Mises yield criterion and because of their specific texture, which develops during the manufacturing process [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys, which have high specific strengths and low densities, are increasingly attracting attention because of their potential for use as materials for lightweight structural components [1][2][3]. However, such alloys exhibit poor formability at low temperatures, owing to the fact that their numbers of activating slip systems are insufficient to satisfy the von Mises yield criterion and because of their specific texture, which develops during the manufacturing process [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Two major approaches are possible that can make Mg alloys have weaker and random textures; 1) the addition of alloying elements, such as rare earth (RE) elements and Ca and 2) the application of severe plastic deformation (SPD) processes. First, it has recently been reported that the alloys containing Ca and RE elements such as Y ad Nd can develop more random textures [5][6][7][8][9][10][11][12][13][14][15], especially a splitting of basal poles from the normal direction (ND) towards the transverse direction (TD) with a broadening of angular distribution of basal poles from the ND towards the TD. Second, it has been reported that SPD processes such as equal channel angular processing, high temperature rolling, differential speed rolling (DSR), and etc, can also develop more random textures [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%